Living in Rural Areas and Self-Employment - Ignacio Belloc; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2022)
This paper examines whether workers living in rural areas are more likely to be self-employed, compared with those in urban areas. We provide evidence for 35 European countries, using the European Working Conditions Survey for the year 2015. We also study the time devoted to market work, and monthly earnings, of self-employed workers in rural and urban areas. Results show that workers in rural areas are more likely to be self-employed than workers in urban areas, although engaging in self-employment in rural areas is associated with significantly lower monthly incomes. We also report differences by welfare state regime. Self-employment is considered a key mechanism to compensate for the difficulty of developing in rural areas, and this paper shows that workers in rural areas in Europe are more likely to be self-employed, despite more challenging working conditions.
Keywords: E24; L26; O18; 330; rural areas; self-employment; europe; earnings; work hour